2018
DOI: 10.1111/imcb.12039
|View full text |Cite
|
Sign up to set email alerts
|

Development of mucosal‐associated invariant T cells

Abstract: Mucosal-associated invariant T (MAIT) cells develop in the thymus and migrate into the periphery to become the largest antigen-specific αβ T-cell population in the human immune system. However, the frequency of MAIT cells varies widely between human individuals, and the basis for this is unclear. While MAIT cells are highly conserved through evolution and are phenotypically similar between humans and mice, they represent a much smaller proportion of total T cells in mice. In this review, we discuss how MAIT ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
45
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 82 publications
(265 reference statements)
6
45
0
Order By: Relevance
“…2,3 The development of this cell type and its selection in the thymus is next explored, an area that can give insight into not only MAIT cell biology but that of other related cell types. 4 The last three reviews look further into the biological roles of these cells. This includes a perspective on the best-described areas of MAIT cell researchnamely antimicrobial defense, based on the specificity of the TCR for the microbially-derived ligand.…”
Section: -563mentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 The development of this cell type and its selection in the thymus is next explored, an area that can give insight into not only MAIT cell biology but that of other related cell types. 4 The last three reviews look further into the biological roles of these cells. This includes a perspective on the best-described areas of MAIT cell researchnamely antimicrobial defense, based on the specificity of the TCR for the microbially-derived ligand.…”
Section: -563mentioning
confidence: 99%
“…This leads naturally on from the cells themselves to what they recognize – a major set of discoveries which has led to an explosion of interest in the field . The development of this cell type and its selection in the thymus is next explored, an area that can give insight into not only MAIT cell biology but that of other related cell types . The last three reviews look further into the biological roles of these cells.…”
mentioning
confidence: 99%
“…This included developmental studies that revealed a three‐step maturation pathway in humans and mice. In mice, these steps are defined as immature stage 1 (CD24 + CD44 − ), intermediate stage 2 (CD24 − CD44 − ) and mature stage 3 (CD24 − CD44 + ) MAIT cells (Figure ) . One factor that was found to be essential for MAIT cell development was the enzyme Drosha .…”
mentioning
confidence: 99%
“…The study by Winter and colleagues adds to growing number of studies elucidating how MAIT cell development is regulated, and offers another checkpoint control factor that regulates this important population of T cells. As miR‐181s are conserved between mice and humans, this study raises the question of whether these regulators also control human MAIT cell development and/or post‐thymic maturation and expansion.…”
mentioning
confidence: 99%
See 1 more Smart Citation